1985
DOI: 10.1193/1.1585265
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of Building Occupants in Earthquakes

Abstract: To be truly effective, earthquake hazard reduction measures must be based on a realistic appraisal of occupants' capabilities and actions during earthquakes. Studies suggest that many overly general beliefs about appropriate response can endanger rather than protect building occupants. We need to analyze occupant actions with respect to hazards posed by the seismic performance of specific building types. This paper will review the findings of recent U.S. studies, discuss the applicability of research from abro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

1989
1989
2015
2015

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 0 publications
0
14
1
Order By: Relevance
“…Therefore, building elements and contents play a clear role in saving or endangering occupants' lives (Durkin and Murakami, 1988). The findings of the study by Durkin (1985) of the El Centro earthquake in California on 15 October 1979 are in need of replication. It is worth pointing out that Durkin showed that 36 per cent of office workers in the Imperial County Services building, which sustained considerable nonstructural damage, reported taking cover under their desks.…”
Section: Human Factorsmentioning
confidence: 95%
See 2 more Smart Citations
“…Therefore, building elements and contents play a clear role in saving or endangering occupants' lives (Durkin and Murakami, 1988). The findings of the study by Durkin (1985) of the El Centro earthquake in California on 15 October 1979 are in need of replication. It is worth pointing out that Durkin showed that 36 per cent of office workers in the Imperial County Services building, which sustained considerable nonstructural damage, reported taking cover under their desks.…”
Section: Human Factorsmentioning
confidence: 95%
“…The importance of knowledge of human behaviour during disasters has been tra ditionally recognised at a meso level, that is, at the level of the community and not of a particular individual. Only a few publications document individual responses during various disasters (Aguirre, 1995;Durkin, 1985;Durkin et al, 1987;Durkin and Murakami, 1988). Aroni and Durkin (1985), in their analysis of earthquake injuries, grouped a multitude of influencing factors into several categories, as described below.…”
Section: Social Science Dimensions Of Sarmentioning
confidence: 99%
See 1 more Smart Citation
“…Even international case studies offer few relevant earthquake datasets. The lack of these datasets and the reporting of earthquake injuries is attributable to the lack of standardized methods to collect data, the interpretations of injury severity, lack of epidemiological data of the patient, and the chaotic nature of post-earthquake situations (Alexander 1985;Durkin 1985;Alexander 1996;Peek-Asa et al 1998;Ramirez and Peek-Asa 2005;Auf der Heide 2006;Stallings 2002;Ardagh et al 2012). 2.…”
Section: Limitations In Model Approachmentioning
confidence: 97%
“…In buildings that are more structurally resilient to lateral forces, operational and functional components (OFCs) are more likely to cause injuries (Ohashi and Ohta 1984;Durkin 1985). OFCs are classified as (1) architectural and non-structural, (2) mechanical, electrical and plumbing, or (3) general building content.…”
Section: Rationalmentioning
confidence: 99%